(untitled) (Indian Journal of Arid Horticulture, 2025)
Eighl isola1cs of fluorescent pseudomonads were isolated from the disease suppressed and identified and characterized by physiological and biochemical and bac1eriological tests. LPK2 aligned to same clus1er (100% boois1rap value) with reference slrains of Pseudomonasjluorescens. All 1he strains of P.jluorescens LPK2 showed IAA production, phospha1e solubilisa1ion, siderophore production and HCN production. Chi1inase activity and P-1,3-glucanase activity was also pronounced in P. j/uorescens LPK2. In dual culture technique, all the slrains of Pseudomonas (LPK I lo LPK8) inhibiled the in vitro growth of F. udum. Maximum inhibition of F. udum recorded in the case of f’.f/uorescens LPK2. Cell free culture filtrale of also restricted lhe hyphal g,owth of F. udum. Scanning electron microscopic studies on morphological fcal r s in the hyphae of F. udum in lhe form of fragmentation and degradation of mycel ia and loss of structural integrity of conid,a of F. udum were clearly observed. In iron supplemented (3011M Fe’’) medium inhibi1ion of the pathogenic fungi was reduced. Under iron-deficient condition, P.fluorescens LPK2 inhibited F. udwn by 65% The inhibition of the pathogen by P.f/uorescens LPK2 under iron-sufficienl conditions was 51%. ·